Self-reported outcomes following lower extremity, carotid and aortic artery disease: protocol for the Danish Vascular (DanVasc) survey - Jes Sanddal Lindholt; Britt Borregaard; Kim Christian Houlind; Marie Dahl; Jacob Budtz-Lilly; Jonas Peter Eiberg; Christian Nikolaj Petersen; Saeid Shahidi (BMJ Open)
Introduction Among lower extremity artery disease (LEAD), symptomatic carotid stenosis (SCS) and abdominal aortic aneurysm (AAA), the disease burden is insufficiently illuminated from a patient and societal perspective. Such knowledge is central to identifying patients at risk of poorer outcomes. Therefore, the Danish Vascular (DanVasc) survey aims to describe self-reported health status, health literacy, medication adherence and loneliness, including changes over time, and investigate characteristics associated with worse self-reported health at baseline and their associations with poorer outcomes within 1 year (healthcare utilisation and mortality) in patients with LEAD, SCS and AAA.Methods and analysis The DanVasc survey, a national prospective cohort study combining survey data measured at several time points with register-based data, includes validated patient-reported outcome measures (PROMs) and ancillary questions developed with patient representatives. Our baseline survey (T0) follows the index contact in vascular outpatient clinics with follow-up surveys determined by the patient’s trajectory: (1) newly referred patients in conservative treatment trajectories; the date for the outpatient visit activates 1-month (T1), 3-month (T2) and 12-month (T3) follow-ups. (2) Patients referred for vascular surgery; the surgery date activates 1-month (T1), 3-month (T2) and 12-month (T3) follow-ups. The included PROMs assess health-related quality of life (HRQoL), anxiety and depression, sleep, frailty status, health literacy, medication adherence and loneliness. For LEAD, a disease-specific PROM evaluates HRQoL. For AAA, disease-specific ancillary questions are added. Additionally, the DanVasc survey includes questions on health behaviour, preventive measures and sexual life. The DanVasc survey will be linked to national registries to obtain socio-demographic information and data on redeemed prescriptions, clinical information, healthcare utilisation, comorbidities and mortality. From December 2023 to December 2024, we aim to recruit approximately 5500 patients from all seven DanVasc surgery departments. Patient characteristics will be reported using descriptive statistics. Changes over time and factors associated with poorer health outcomes will be analysed using linear, logistic and Cox proportional hazard models, presented as univariate and multivariate regressions.Ethics and dissemination Approval for the collection of medical record data was granted by the Central Denmark Region, acting on behalf of all Danish regions (record 1-45-70-94-22). Consent to participate is obtained prior to answering the survey. Results will be disseminated through peer-reviewed scientific publications and conference presentations, and findings will be shared with patients and relevant stakeholders via public and social media.